Bæredygtig mobilitet i København med udgangspunkt i ITS / Sustainable mobility in Copenhagen enabled by ITS - Gaml, Mads; van Koningsbruggen, Paul (Proceedings from the Annual Transport Conference at Aalborg University, 2017)
As with many growing cities in the World, Copenhagen has to cope with a growing population and corresponding growing traffic demand. What is the Copenhagen way to deal with the challenges in urban mobility that comes with this growth? The first answer is concretized in a clear political goal (CO2 neutral in 2025). The second answer is formulated in a new political vision titled Community Copenhagen. The vision is an open invitation to all who use the city to build on 'a living and vibrant city', 'a city with edge' and 'a responsible city' together. The new political vision asks for a new take on multimodal traffic management that interacts directly with citizens and strengthens green mobility, thereby paving the path for sustainable mobility in daily life in Copenhagen – basically been a Smart City. This paper elaborates on the intelligent traffic solutions that enable sustainable mobility in Copenhagen. This is an edited and updated version of a paper presented at the ITS European Congress with the title: ”Intelligent Traffic Solutions for sustainable urban mobility in Copenhagen”.